TOWARDS INTEGRATED DISASTER MANAGEMENT: A REVIEW OF AI, BLOCKCHAIN, AND DIGITAL TWIN TECHNOLOGIES FOR SMART RESILIENCE - Karaduman, Ozgur (My University, 2025)
Disaster management is undergoing a paradigm shift driven by the convergence of emerging digital technologies. Traditional systems often operate as non-integrated structures, which limits their capacity to respond and adapt in multi-hazard scenarios. In this context, Artificial Intelligence (AI), Blockchain, and Digital Twin (DT) technologies have emerged as transformative components in building smart, resilient disaster response frameworks. This review aims to synthesize the current state of research and applications involving these three technologies, with a particular focus on their integration potential for cohesive, secure, and adaptive disaster management systems. The study systematically examines how AI contributes to predictive analytics and decision-making, how Blockchain enhances data integrity, transparency, and coordination, and how DT enables real-time simulation and scenario planning. It also explores the interplay between these technologies and highlights emerging frameworks that attempt to combine them in unified architectures. Furthermore, key technical and operational challenges such as interoperability, data standardization, and real-time synchronization are discussed. By analyzing existing solutions and identifying critical research gaps, this review provides a roadmap toward integrated, intelligent disaster management systems. The review emphasizes the unique contributions of each technology and underscores the need for interoperability, effective data governance, and real-time decision support in integrated disaster management.
Keywords: Artificial intelligence; disaster management; blockchain-based coordination; digital twin simulation; smart resilience